2014
DOI: 10.1099/mic.0.081133-0
|View full text |Cite
|
Sign up to set email alerts
|

The RcsCDB regulatory system plays a crucial role in the protection of Salmonella enterica serovar Typhimurium against oxidative stress

Abstract: Dps, the most abundant protein during the stationary growth phase, in Salmonella enterica is required for resistance to reactive oxygen species produced by the host during infection. It has been reported that in Salmonella dps expression is controlled by RpoS and Fur proteins. However, the regulation and function of Dps remain to be resolved. In the present work we demonstrate that activation of the complex RcsCDB regulatory system increases dps expression during exponential growth of Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In drug-tolerant E. coli cells, SOD and catalase have been shown to have a protective function (50). In other gastrointestinal pathogens, such as S. Typhimurium, many genes must be expressed in order to inactivate ROS, in a process controlled by regulons, such as SoxRS, OxyR, S, E, SlyA, and RecA, as well as the Dps protein, which halts bacterial growth under the control of the factor RpoS (51) (Fig. 2).…”
Section: Oxidant Tolerance (Ros Response)mentioning
confidence: 99%
“…In drug-tolerant E. coli cells, SOD and catalase have been shown to have a protective function (50). In other gastrointestinal pathogens, such as S. Typhimurium, many genes must be expressed in order to inactivate ROS, in a process controlled by regulons, such as SoxRS, OxyR, S, E, SlyA, and RecA, as well as the Dps protein, which halts bacterial growth under the control of the factor RpoS (51) (Fig. 2).…”
Section: Oxidant Tolerance (Ros Response)mentioning
confidence: 99%
“…The RcsCDB is an unorthodox signaling system which consists of the transmembrane sensor kinases RcsC and RcsD and the response regulator RcsB (Clarke, 2010;Pescaretti Mde et al, 2013). In Salmonella and E. coli, RcsB induces expression of genes involved in capsular polysaccharide synthesis, responses to oxidative stress, resistance to antimicrobial peptides and systemic colonization of mice (Gottesman et al, 1985;Erickson and Detweiler, 2006;Clarke, 2010;Farizano et al, 2014). RcsB represses flagellar motility and virulence genes on the Salmonella Pathogenicity Island II (Gottesman et al, 1985;Wang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the SlyA repression effect on rcsB, we used another RcsB-dependent gene, dps (32). When the levels of dps::lacZY transcription were determined, we observed that slyA overexpression decreased dps expression in the wild type but not in the rcsB strain (Fig.…”
Section: Figmentioning
confidence: 91%